Acne Vulgaris - An Overview (Homoeopathy for All, 2022)
Acne is also known as pimple in the  layman terms.  Acne is one of the commonest  skin disorders – if not the  commonest, it has been evident  in 70% of population at some  stage during their adolescence,  occurs mainly due to occlusion of  sebaceous gland which may be due  hair, sebum, dirt including bacteria  and dead skin cells.  It’s a chronic inflammatory  disease of the pilosebaceous unit.  Open pores when get blocked  usually present as open comedone  (black head) and closed comedone  (white head).  About 80% of people ages 11 to  30 will have some or the other mild  form of acne, and most people are  affected by it at some point in their  lives.  Area affected mostly includes  face, arms, chest, and upper back.
Keywords: skin; upper back; Pathophysiology